PENGARUH PEMANFAATAN INTERNET TERHADAP HASIL BELAJAR SISWA SMPN 2 BINTUNI PAPUA BARAT - Manibuy, Loria I (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to determine the effect of internet use on student learning outcomes at SMP Negeri 2 Bintuni West Papua. This research is quantitative. This research work was carried out at SMP Negeri 2 Bintuni from February to March 2024. Random sampling was used to select 126 people. Data collection uses observation, questionnaires and documentation. Data analysis uses descriptive and inferential statistical analysis. The research results show that the indicators used for each variable show that internet use is in the very good category, based on the coefficient of determination test, the magnitude of the influence is strong or high between the two variables. Thus, the conclusion of the research is that internet use has a large or very high influence on student learning outcomes at SMP Negeri 2 Bintuni West Papua.